2019
DOI: 10.3390/cancers11121933
|View full text |Cite
|
Sign up to set email alerts
|

SerpinB3 Differently Up-Regulates Hypoxia Inducible Factors -1α and -2α in Hepatocellular Carcinoma: Mechanisms Revealing Novel Potential Therapeutic Targets

Abstract: Background: SerpinB3 (SB3) is a hypoxia and hypoxia-inducible factor (HIF)-2α-dependent cysteine-protease inhibitor up-regulated in hepatocellular carcinoma (HCC), released by cancer cells and able to stimulate proliferation and epithelial-to-mesenchymal-transition. Methods: In the study we employed transgenic and knock out SerpinB3 mice, liver cancer cell line, human HCC specimens, and mice receiving diethyl-nitrosamine (DEN) administration plus choline-deficient L-amino acid refined (CDAA) diet (DEN/CDAA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…NEDD8 stabilised HIF-1α under both normoxia and hypoxia in VHL deficient cells, suggesting a VHL-independent process [ 122 ]. More recently it was reported that SerpinB3 (SB3), a hypoxia and HIF-2α-dependent cysteine-protease inhibitor, can directly neddylate and stabilise HIF-2α, which led to an upregulation of its target genes in liver cancer cells [ 123 ]. Overall, these reports underline the role of neddylation in HIF regulation, but none of the reports have yet shown the exact sites within the HIF proteins where the neddylation occurs.…”
Section: Uncharacterised Ptmsmentioning
confidence: 99%
“…NEDD8 stabilised HIF-1α under both normoxia and hypoxia in VHL deficient cells, suggesting a VHL-independent process [ 122 ]. More recently it was reported that SerpinB3 (SB3), a hypoxia and HIF-2α-dependent cysteine-protease inhibitor, can directly neddylate and stabilise HIF-2α, which led to an upregulation of its target genes in liver cancer cells [ 123 ]. Overall, these reports underline the role of neddylation in HIF regulation, but none of the reports have yet shown the exact sites within the HIF proteins where the neddylation occurs.…”
Section: Uncharacterised Ptmsmentioning
confidence: 99%
“…Additionally, SERPINB3 can protect cancer cells from oxidative stress through the up-regulation of HIF-1α transcription and HIF-2α stabilization to favor tumor growth [ 172 , 173 ]. In chronic liver damage, this serpin can lead to HCC promotion through the inhibition of apoptosis, EMT induction, and increase in cell proliferation and invasiveness [ 174 ].…”
Section: Promising Proteomic Biomarkers Of Hccmentioning
confidence: 99%
“…Likewise, neddylation modification of cullin2 alters the activity of CRL2 and eventually influences the stability of HIF1α (109) (Figure 2). Recently, Cannito et al (110) have suggested that SerpinB3, a serine protease inhibitor, can stimulate proliferation of hepatic tumor cells and subsequently facilitate HCC progression by enhancing the stabilization of HIF2α by promoting the direct and selective neddylation of HIF2α (111).…”
Section: Neddylation and Hccmentioning
confidence: 99%